In the Name Religion and Defending Women; Experiences of Three Pesantren Women in Indonesia Local Elections - Abdul Chalik (JPW (Jurnal Politik Walisongo), 2023)
The leadership of Indonesian Muslim women experienced a development, marked by the ever extensive political roles. Some previous researches state that the factor of familial closeness (political dynasty), gender, collusion, sexiness and piety marketing stimulate women’s election in political contestations. But these reasons are not enough to explain the reason for women’s roles in the public, especially women of pesantren (Islamic boarding schools). We suggest that women’s courage in the struggle for the political position is due to their desires to strive for women's rights that are ignored and not comprehensively understood by male leaders. The existence of the thought that women can (only) ‘understand women’ becomes the reason why regional leaderships are also seized by women. The article also shows the ability to integrate spirituality towards public roles by utilizing their social capitals. This paper also counters some arguments that women always lose in public sectors in political sector fights as they are under the shadow of their husbands or men.